Diode-Laser Induced Fluorescence Spectroscopy of an Optically Thick Plasma in Combination with Laser Absorption Spectroscopy - S. Nomura; T. Kaneko; G. Ito; K. Komurasaki; Y. Arakawa (Journal of Spectroscopy)
Distortion of laser-induced fluorescence profiles attributable to optical absorption and saturation broadening was corrected in combination with laser absorption spectroscopy in argon plasma flow. At high probe-laser intensity, saturated absorption profiles were measured to correct probe-laser absorption. At low laser intensity, nonsaturated absorption profiles were measured to correct fluorescence reabsorption. Saturation broadening at the measurement point was corrected using a ratio of saturated to non-saturated broadening. Observed LIF broadening and corresponding translational temperature without correction were, respectively, 2.20±0.05 GHz and 2510±100 K and corrected broadening and temperature were, respectively, 1.96±0.07 GHz and 1990±150 K. Although this correction is applicable only at the center of symmetry, the deduced temperature agreed well with that obtained by LAS with Abel inversion.